A Systematic Literature Review of Sustainable Consumer Behaviours in the Context of Industry 4.0 (I4.0) - Korkmaz, Ayten Nahide; Altan, Meral Uzunoez (MDPI, 2024)
Sustainability and related issues are widely accepted as vital themes in contemporary fields. These include the idea of developing products and services necessary for individuals to lead sustainable lives into the future in Industry 4.0 (I4.0), the main focus of which is digitalization. Also, the notion of Sustainable Consumption (SC) is related to the Sustainability Development Goals (SDGs), which comprise SC and production motives. The methodology of this study involved analysing data from a bibliometric review, which was obtained from different themes within environmentally friendly and ecofriendly consumption sources. We searched a key theme, SC, in the Web of Science (WoS) database and obtained 1451 documents. A total of 1005 documents were selected. In the next stage, we searched for two key words, environmentally consumer behaviour and eco-friendly consumer behaviour; 258 studies were obtained from the WoS database. This paper represents a thorough literature review of the line between consumers and SC. The aim of this study is to underline the level of awareness of environmentally friendly and ecofriendly consumption in the I4.0 period by selecting and examining articles published over the past 10 years. The final aim of this work is to provide suggestions based on gaps in the literature.
Keywords: consumer behaviours; eco-friendly; environment; environmental approaches; sustainability; sustainable consumption; Industry 4.0 (I4.0); PRODUCT CONSUMPTION; CIRCULAR ECONOMY; GREEN PRODUCTS; MOTIVATIONS; FRAMEWORK; ATTITUDES; ACHIEVE; VALUES; Science & Technology - Other Topics; Environmental Sciences & Ecology